Can East Asia Compete : Innovation for Global Markets - Yusuf, Shahid; Evenett, Simon J. (Washington, DC: World Bank and Oxford University Press, 2013)
East Asian economies are at different stages of development, but to preserve-and to increase-their competitiveness through innovation and the opportunities presented by information and communication technologies (ICT), they need to move quickly to frame and implement policies in five areas. Reform and restructuring of the banking system are matters of priority: Second, corporate governance in East Asia has lagged where management skills have fallen behind, and the pressure on managements to pursue strategies aimed at maximizing shareholder value are often weak. Policies to build institutions, both legal and financial, that shore up shareholders' rights and sharpen the market for corporate control would significantly augment management capabilities. Third, in an increasingly knowledge-based economy, the supply of workers with the requisite skills and penchant for creativity will determine how much innovation takes place and how it is used to enlarge market shares. The situation requires reinforcing secondary and tertiary education, which influence analytical skills and the aptitude to innovate. Fourth, although computer use in East Asia is spreading and telecommunications facilities are improving daily, e-business and e-commerce are greatly hampered by the inadequacy of supporting services such as secure credit card transactions, fulfillment, logistics, and legal services. Finally, trade liberalization, preferably multilateral trade reform, needs to be actively pursued.